Elimination of T cell reactivity to pancreatic β cells and partial preservation of β cell activity by peptide blockade of LFA-1:ICAM-1 interaction in the NOD mouse model - Dotson, Abby L (Clinical immunology (Orlando, Fla.), 2013)
Copyright © 2013 Elsevier Inc. All rights reserved.